2019
DOI: 10.14715/cmb/2019.65.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous responses of photosystem II and soluble proteins of rapeseed to cold acclimation

Abstract: This experiment was conducted to assess the quantitative and qualitative changes in soluble proteins as well as some chlorophyll fluorescence parameters in the leaves of a winter canola (Brassica napus L., cv. Licord) under continuous low temperature. Over the experiment, seedlings were initially grown at 15/10 °C (d/n). At fourth fully expanded leafy stage (day 30), a part of the plants were transferred to 4/2°C for 4 weeks. Plants were sampled for protein extraction from leaves in which chlorophyll fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…Soluble protein was an important osmoregulatory substance and nutrient in plants. Most soluble proteins were enzymes involved in various metabolisms, which can regulate the growth of plants and protect plants against stress [36]. Results showed that the content of soluble protein in JRF11-20-treated plants was significantly increased compared with the control (Figure 5D).…”
Section: Effects Of Paraphaosphaeria Strain Jrf11 On Physiology Of To...mentioning
confidence: 96%
“…Soluble protein was an important osmoregulatory substance and nutrient in plants. Most soluble proteins were enzymes involved in various metabolisms, which can regulate the growth of plants and protect plants against stress [36]. Results showed that the content of soluble protein in JRF11-20-treated plants was significantly increased compared with the control (Figure 5D).…”
Section: Effects Of Paraphaosphaeria Strain Jrf11 On Physiology Of To...mentioning
confidence: 96%
“…In our study, the F v /F m , Y(II), and qP values of A. thaliana showed a decreasing trend under the stress treatments compared to CK (Figures 4K-M, 5K-M and 6K-M). Arminian et al [38] found that the chl fluorescence parameters of canola (Brassica napus L.) leaves decreased during cold. Li et al [39] found that the F v /F m and qP of two different varieties of cucumber (Jinchun No.4, Zhongnong No.12) under high temperatures both decreased.…”
Section: The Function Of the Cfchlm Gene In Photosynthesismentioning
confidence: 99%
“…Oxidative damage was estimated by measuring the content of MDA as described previously (Du et al, 2010). The content of soluble protein (SP) was measured as previously described (Arminian and Dehghani Bidgoli, 2019). The activity of ROS scavenging enzymes, such as ascorbate peroxidase (APX) activity, peroxidase (POD) activity (Quiroga et al, 2000), superoxide dismutase (SOD) activity, catalase (CAT) activity, were measured as described in previous studies (Quiroga et al, 2000;Yao et al, 2011;Zhang et al, 2013).…”
Section: Measurements Of Phenotypic and Physiological Traitsmentioning
confidence: 99%